4s-27=-31+6s

Simple and best practice solution for 4s-27=-31+6s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4s-27=-31+6s equation:


Simplifying
4s + -27 = -31 + 6s

Reorder the terms:
-27 + 4s = -31 + 6s

Solving
-27 + 4s = -31 + 6s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-6s' to each side of the equation.
-27 + 4s + -6s = -31 + 6s + -6s

Combine like terms: 4s + -6s = -2s
-27 + -2s = -31 + 6s + -6s

Combine like terms: 6s + -6s = 0
-27 + -2s = -31 + 0
-27 + -2s = -31

Add '27' to each side of the equation.
-27 + 27 + -2s = -31 + 27

Combine like terms: -27 + 27 = 0
0 + -2s = -31 + 27
-2s = -31 + 27

Combine like terms: -31 + 27 = -4
-2s = -4

Divide each side by '-2'.
s = 2

Simplifying
s = 2

See similar equations:

| 7.50x=750 | | h=-16t^2+75t+8 | | 5y=1000 | | 6*1r=36 | | y=3sin(x) | | 2(3+2x)-1=17 | | 5y-(8-y)=2[-4-(3+5y)-13] | | 3(b+2)=4b-10 | | 10+3[x+2]=31 | | -5x+6=3x-9 | | log(12x+2)=log(2x-1)+1 | | 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 |

Equations solver categories